Spatiotemporal variations of tidal flat landscape patterns and driving forces in the Yangtze River Delta, China - Cheng, Shuo; Zeng, Xu; Wang, Zihan; Zeng, Cong; Cao, Ling (Frontiers in Marine Science, 2023)
As a crucial coastal wetland habitat in the transition zone between land and sea, global tidal flats have severely declined by 16% over the last two decades under the dual threats of intense human activities and climate change. The Yangtze River Delta of China, the largest estuary in the western Pacific Ocean, has abundant mudflat resources and a dense human population. It also has some of the most prominent conflicts between economic development and ecological conservation. The current lack of understanding of landscape patterns and influencing factors of the Yangtze River Delta mudflats has severely hampered the region’s ecological conservation and restoration efforts. Based on Landsat time-series images, this study generated a 30-m spatial resolution map of mudflats in the Yangtze River Delta, which shrank by 47% during 1990–2020, with a higher density of mudflat loss in Yancheng and Nantong cities of the Jiangsu province and Hangzhou, Shaoxing, and Ningbo cities of the Zhejiang province. Landscape indices, such as the patch density of tidal flats, have gradually changed since 2000, with most of them showing significant changes in 2010. Mudflats in Lianyungang, northwestern Yancheng, Nanhui, Jiaxing, and Hangzhou showed sharp negative changes in landscape characteristics. Natural and anthropogenic factors had synergistic effects on the above changes in mudflat landscape patterns in the Yangtze River Delta. Mudflat landscape features were mainly influenced by population growth, economic development, reclamation, sediment discharge, and air temperature. Based on the evolving characteristics of mudflat landscape patterns, we recommend improving mudflat landscape management and planning by strengthening mudflat policies, laws, and regulations, developing countermeasures against threats from major stressors, and enhancing the effectiveness of nature reserves for mudflat protection.